Occupational recognition and immigrant labor market outcomes - Herbert Brücker; Albrecht Glitz; Adrian Lerche; Agnese Romiti (Deutsches Institut für Wirtschaftsforschung (DIW), 2018)
In this paper, we analyze how the formal recognition of immigrants' foreign occupational qualifications afects their subsequent labor market outcomes. The empirical analysis is based on a novel German data set that links respondents' survey information to their administrative records, allowing us to observe immigrants at monthly intervals before, during and after their application for occupational recognition. Our findings show substantial employment and wage gains from occupational recognition. After three years, the full recognition of immigrants' foreign qualifications increases their employment rates by 24.5 percentage points and raises their hourly wages by 19.8 percent relative to immigrants without recognition. We show that the increase in employment is largely driven by a higher propensity to work in regulated occupations. Relating our findings to the economic assimilation of immigrants in Germany, we further document that occupational recognition leads to substantially faster convergence of immigrants' earnings to those of their native counterparts.
Keywords: J15; J24; J44; J61; 330; Occupational Recognition; Immigrants; Labor Markets